Computational methods in engineering - Venkateshan, S. P. 4 0 16; Swaminathan, Prasanna; 5 (Kidlington, Oxford : Academic Press, 2014)
Computational Methods in Engineering brings to light the numerous uses of numerical methods in engineering. It clearly explains the application of these methods mathematically and practically, emphasizing programming aspects when appropriate. By approaching the cross-disciplinary topic of numerical methods with a flexible approach, Computational Methods in Engineering encourages a well-rounded understanding of the subject. This book's teaching goes beyond the text-detailed exercises (with solutions), real examples of numerical methods in real engineering practices, flowcharts, and MATLAB codes all help you learn the methods directly in the medium that suits you best. Balanced discussion of mathematical principles and engineering applications. Detailed step-by-step exercises and practical engineering examples to help engineering students and other readers fully grasp the concepts. Concepts are explained through flowcharts and simple MATLAB codes to help you develop additional programming skills.
Preliminaries -- Module 1. System of equations and eigenvalues -- Solution of linear equationa --Computational eigenvalues -- Solution of algebraic equations -- Module 2. Interpolation, differentiation and integration -- Interpolation -- Interpolationin in two and three dimensions -- Regression or curve fitting -- Numerical differentiation -- Numerical integration -- Module 3. Ordinary differntial equations -- Initial value problems -- Boundary value problems (ODE) -- Module 4. Partial differential equations -- Introductio ot PDEs -- Laplace and Poisson equations -- Advection and diffusion equations -- Wave equation -- Beyond the book: the way ahead.
June 2013
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Data processing. -- Engineering mathematics.;Engineering mathematics -- 20; 20; 2